Urban Metabolism of Energy Consumption in Cities (Journal of Engineering, 2024)
The idea of the research came from the importance of the issue of energy consumption in cities as the cities of the world, in general, and Iraqi cities in particular, face significant environmental challenges from carbon emissions. The research problem revolves around the increase in the consumption of non-renewable energy using traditional methods, as is the case in the city of Zaafaraniya and this leads to an increase in the carbon footprint locally and globally and poses a threat to the lives of residents. This requires verification to find solutions through understanding the city’s input and output processes as the urban metabolism. The research will summarize the concept of greenhouse gases, types of energy sources, measure the energy footprint of the case study, and the relationship of land use to energy. The research provided results that indicate the continuing population increase in cities, as the population of the Al- Zaafaraniya reached (889,000 people) in 2023. This was related to a continuous rise in energy consumption. The electricity footprint amounted to (491,507 tCO2) which is the highest, and the fuel footprint of gasoline consumption amounted to (477,988 tCO2). At the same time, the diesel footprint amounted to (411,877 tCO2). There is a variance between different land uses. Residential use consumes 40% of energy. By following strategies to reduce energy consumption through an efficient city layout that encourages public transportation, walking, waste recycling, and using clean, renewable energy. It leads to lowering the carbon footprint.